Stress-dependent shear transformation zone in NiNb thin film metallic glass and its correlation with deformation mode transition. (September 2016) - Wang, C.; Cao, Q.P.; Wang, X.D.; Zhang, D.X.; Qu, S.X.; Jiang, J.Z.
Abstract: Stress effect on shear transformation zone (STZ) in Ni60 Nb40 thin film metallic glass was investigated. Through nanoindentation tests on the bent specimen, it was found that compressive stress decreased the STZ volume and activation energy in comparison with tensile stress and hence easy activation of STZs lowered the tendency of shear localization, which resulted in increased number and reduced length of serration. Therefore, easier STZ activation conduced to the larger critical size for deformation mode transition from highly-localized to non-localized.